Los determinantes de la legitimidad gubernamental: el sexenio de Enrique Peña Nieto - Somuano, Ma. Fernanda (El Colegio de México A.C., 2020)
The objective of this study is to explore from an empirical perspective the grounds for governmental legitimacy during the administration of Enrique Peña Nieto. It uses individual perception and attitude data to analyze the factors that led citizens to perceive greater or lesser legitimacy  in the government as a whole (not only that of President Peña Nieto) and which factors influence changes in this perception. With data taken from the Barómetro de las Américas (2012, 2014 and 2017), the paper shows that both in 2014 and in 2017 presidential approval is the factor that has greatest influence on governmental legitimacy. Citizens who reported greater levels of satisfaction with public schools and who identified with the PRI party also tended to perceive greater governmental legitimacy.